2019
DOI: 10.1088/1755-1315/388/1/012046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foliar nutrition of nano-fertilizers and amino acids on growth and yield of wheat.

Abstract: A field experiment was carried out at the Extension farm in Province 41 of Husseiniya, Babylon Governorate to study the effect of foliar nutrition with some of nano-fertilizers and nano-amino acids on growth and yield of wheat cultivar Adana 99. The experiment included 8 treatments of Nano chelated super fertilizer (NCSF), nano-amino acids (AA), nano potassium K (NK),di (NCSF +NAA),(NCSF +NK), (NAA+NK), tri (NCSF +NAA+NK) and spray with water only as control for comparison with three replicates in a simple one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 21 publications
6
39
0
Order By: Relevance
“…Enhancement of many physiological parameters such as enhanced photosynthetic activity and nitrogen metabolism by metal-based nano-materials in a few crops (Sekhon, 2014). The obtained results are in a good accordance with those recorded by Ali and Al-Juthery (2017) and Al-juthery et al (2019).…”
Section: Effect Of K Nano-fertilizationsupporting
confidence: 87%
“…Enhancement of many physiological parameters such as enhanced photosynthetic activity and nitrogen metabolism by metal-based nano-materials in a few crops (Sekhon, 2014). The obtained results are in a good accordance with those recorded by Ali and Al-Juthery (2017) and Al-juthery et al (2019).…”
Section: Effect Of K Nano-fertilizationsupporting
confidence: 87%
“…Potato (Solanum tuberosum L.) is considered one of the most important vegetable crops in the world in terms of production and cultivated area, it belongs to the Solanaceae family, which includes about 90 genera and about 2000 species [1,2]. Cultivated areas of potato crop in Iraq are increasing, however, that the produced quantities do not meet the requirements of the Iraqi consumers.…”
Section: Introductionmentioning
confidence: 99%
“…It is also involved in the biological resistance for some pests and plant diseases [9,10]. The concept of integrated fertilization has emerged, which is a combination of chemical, organic and bio-fertilization in order to rationalize the use of chemical fertilizers and compensating them with natural fertilizers for the purpose of increasing yield and improving quality [1].…”
Section: Introductionmentioning
confidence: 99%
“…There may be some another reason that higher dose of nano nitrogen fertilizer helped in increasing the size and efficacy of the source, which caused an increasing in the representation of nutrients that helped to form a good downstream and then a heaver grain weight (Sharifi and Namvar, 2016). Jian et al (2008), Fan et al (2012), Prasad et al (2012), Morteza et al (2013), Kole et al (2013), Manikandan and Subramanian (2016), Hagab et al (2018), Anupama et al (2020) and Al-Juthery et al (2019) reported similar findings.…”
Section: Yieldmentioning
confidence: 80%